Marathon running and cell-cycle arrest biomarkers of acute kidney injury. Issue 1 (January 2023) - Leckie, Todd; Fitzpatrick, Daniel; Richardson, Alan J.; Hunter, Alex; Bains, Sonia; Grimaldi, Rachael; Galloway, Rob; Forni, Lui G.; Hodgson, Luke E.
Abstract: Objectives: Endurance exercise is known to cause a rise in serum creatinine. It is not known to what extent this rise reflects renal stress and a potential acute kidney injury (AKI). Increases in Insulin Like Growth Factor Binding Protein 7 (IGFBP7) and Tissue Inhibitor of Metalloprotinases-2 (TIMP-2), urinary biomarkers of cell cycle arrest and renal stress, are associated with the development of AKI in clinical populations. Design: Repeated measures study. Methods: Runners were recruited at the 2019 Brighton Marathon (UK) and provided urine and blood samples at baseline, immediately post-race and 24 h post-race. Serum creatinine, urinary creatinine and urinary IGFBP7 and TIMP-2 were analysed from the samples. Results: Seventy nine participants (23 females, 56 males), aged 43 ± 10 yrs. (mean ± SD), finish time 243 ± 40mins were included for analysis. Serum creatinine increased over the race by 40 ± 26% ( p < 0.001), TIMP-2 increased by 555 ± 697% ( p < 0.001) and IGFBP7 increased by 1094 ± 1491% ( p < 0.001) over the race. A subset of twenty-two participants supplied samples 24 h post-race, reporting values similar to baseline for all variables. Conclusions: This study is the first to report large rises in IGFBP7 and TIMP-2 following marathon running. This suggests that rises in creatinine are not fully explained by changes in production and clearance and marathon running induces a state of kidney stress and potential injury.